2020
DOI: 10.1364/josaa.409955
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of frequency dependent differential photoacoustic cross-section data for source size estimation

Abstract: A frequency dependent differential photoacoustic cross-section (DPACS) over a large frequency band (100–1000 MHz) was computed, and subsequently, morphological parameters of a photoacoustic (PA) source were quantified. The Green’s function approach was utilized for calculating the DPACS for spheroidal droplets with varying aspect ratios, Chebyshev particles with different waviness and deformation parameters, and normal red blood cells and cells affected by hereditary disorders (e.g., spherocytosis, elliptocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The standard approach is to iteratively expand Eq. ( 5) to obtain a faithful solution [4,5]. It has been recently shown that an approximate solution can also be obtained by consiedering only the first term of Eq.…”
Section: Theoretical Components and Numerical Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard approach is to iteratively expand Eq. ( 5) to obtain a faithful solution [4,5]. It has been recently shown that an approximate solution can also be obtained by consiedering only the first term of Eq.…”
Section: Theoretical Components and Numerical Implementationmentioning
confidence: 99%
“…Efforts have been made to measure optoacoustic (OA) signals from individual cells in vitro [3]. Several theoretical studies have also been conducted to examine OA emission from normal and pathological cells both in the time and frequency domains [4]. It has been concluded that the OA spectral features depend upon the size and shape of the source and also on the direction of the measurement.…”
Section: Introductionmentioning
confidence: 99%